Elaboration, characterization and color stability of an isotonic beverage based on whey permeate with carotenoid powder from pequi (Research, Society and Development, 2021)
The aim of our research was to elaborate, characterize and evaluate the stability under light/darkness and different temperatures (4 and 25 ºC) of the color of an isotonic beverage based on whey permeate with carotenoid extract powder from pequi, and verify its microbiological safety and sensory acceptance. The 3% (w/v) concentration of powdered carotenoid from pequi was chosen because it has osmolality (314.89 mOsmol/L) in the range of hydroelectrolytic beverages and light-yellow tint. The beverage was evaluated for minerals Na (662 mg/L), K (1363.73 mg/L), total carotenoids (75.9 mg/L) and antioxidant capacity by the radicals ABTS (10.79 μmol equivalent Trolox/100 mL) and DPPH (73.38 μmol equivalent Trolox/100 mL), had good sensory acceptance by athletes and remained within microbiological criteria during stability study. The color coordinate L* has undergone less change and C*, greater change. The condition darkness at 4 ºC showed less change in yellow tint, for more than 30 days (t1/2=121.6 day). Due to its characteristics, the beverage has potential benefits for consumption by athletes, because besides being isotonic, it has bioactive properties of pequi carotenoids and natural constituents of whey permeate. The use of permeate, often discarded as effluent, has benefits for the environment.